Aplikasi Web Service Berbasis Android untuk Pencarian Kost Lingkungan Kampus Universitas Indraprasta PGRI - Purwanti, Purwanti; Nazelliana, Dian (Jurnal Informatika Universitas Pamulang, 2021)
Human needs are the reason technology is developing rapidly. One of the benefits of technological development is making information very easy to obtain. Everyone can get various kinds of information, such as searching for a list of houses, rented houses to boarding houses. Many people get that information easily, but not a few people have difficulty getting the same information. One example that often occurs is overseas students who find it difficult to get boarding information. Indraprasta University students complain that it is difficult to get information on boarding houses that are close to campus. From this problem, it prompted the author to create an Android-based Boarding House Search Application. In making this application the author uses Android Studio as a code editor, and exchanges data on the web service using JSON. Searching for boarding houses in this application uses two ways, first a boarding search based on a list and second a boarding house search based on the user's closest location. The menu on the main page makes this application easy to use by anyone.